Transition from physical to virtual classroom amidst COVID-19 crisis: Analyzing students' perspective to drive improvement in the current online teaching methodology - Jyoti Chopra; Anita Rani; Shloak Chopra; Punita Manik; Rana Ravneesh Singh (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Among the COVID crisis, medical education is forced to shift to the virtual mode, for which neither the students nor the teachers are prepared. Currently, we replaced traditional classroom teaching (CT) by live online classes (LOC), power-point presentations with voiceovers (UPV), or only power point presentations (UP). Uncertainty of this situation necessitates analysis of the experiences of its stakeholders to improve the implemented online teaching methodologies in coming time. The present study aims to analyze and compare the effectiveness of online teaching methodologies among themselves and against traditional CT. MATERIALS AND METHODS: A cross-sectional, survey based, observational study was conducted on 250 MBBS first year students after 1 month of implementation of online teaching program. Responses were collected on Likert scaling from 1 to 5, and data were analyzed using the Kruskal-Wallis H-test, ANOVA with multiple comparisons post hoc Turkey test, and an independent t-test. RESULTS: The students perceived that the understanding, convenience for attending class, notes-taking, visibility, audibility, raising queries and overall experience was best in traditional setup. The understanding of the topic and overall experience of the students was not affected by gender. Internet connectivity problem popped up as the major issue that adversely affected the online teaching experience. CONCLUSIONS: Majority of students perceived that the traditional CT is best, but at the same time, they felt that a combination of live online classes and power point presentations with voice over can replace the traditional online classes.